First record of the genus Tetradonia Wasmann, 1894 (Coleoptera: Staphylinidae: Aleocharinae) in Colombia, with description of two new species - Gualdrón-Díaz, Juliette C.; Chani-Posse, Mariana R. (Zootaxa, 2024)
This paper describes and illustrates two new species of the genus Tetradonia Wasmann, 1894 (Staphylinidae: Aleocharinae), discovered in the Eastern Andes of Colombia: T. vonbeerensis Gualdrón-Diaz & Chani-Posse sp. n. and T. ramirezi Gualdrón-Diaz & Chani-Posse sp. n. This report marks the first documented presence of the genus in Colombia. Furthermore, our findings contribute to an increased understanding of Neotropical Tetradonia species, bringing the total known species count to forty-one.